KONSEP PENDIDIKAN ANAK USIA DINI DALAM PERSPEKTIF ISLAM - Putri, Hadisa (Khazanah: Jurnal Studi Islam dan Humaniora, 2016)
The purpose of this paper is that early childhood education in the Islamic view is to maintain, assist the growth and development of human nature owned by children, so that the soul of a child born in the state of nature is not polluted by worldly life that can make children as Jews, Christians or Magi. Or in other words that early childhood education in Islamic education aims to instill Islamic values to children from an early age, so that in further development the child becomes a Muslim man who is kaffah, who believe and piety to Allah SWT. In the journal paper will describe how the concept of Early Childhood education in Islamic perspectives both from curriculum, learning materials, methods and environment that affect the Early Childhood from the perspective of Islamic education. The result of the discussion that is proposed is the educational substance that must be given to the child covering the whole teachings of Islam that can be broadly grouped into three, namely aqidah, worship and morals and equipped with education to read Al-Qur'an. The material of Islamic education is the same as Islamic religious material, but about health and body hygiene, body movement (sports), learning to play with peers, learning to read and writing latin, study counting, drawing, folding are also conveyed. While the methods of Islamic education applied to early childhood education activities such as exemplary methods, education with practice and practice, educate through games, songs, and stories, and educate with targhib and tarhib.